2022
DOI: 10.1037/cbs0000270
|View full text |Cite
|
Sign up to set email alerts
|

Mock juror decision-making in a self-defence trial involving police use of force.

Abstract: Previous research has found that citizens' attitudes concerning police legitimacy influence their behavior toward the police. However, this relationship has yet to be studied in the context of a jury trial involving police use of force (UoF). The primary goal of this article is therefore to examine whether mock jurors' race, along with their perceptions of police legitimacy, predict verdict decisions in trials involving police UoF. We hypothesized that participants' perceptions of police legitimacy would be si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 52 publications
2
7
3
Order By: Relevance
“…This conflicts with previous jury research conducted by Ewanation, Maeder, and Yamamoto (2021), who found that the more legitimate participants believed the police to be, the more likely they were to find a defendant guilty of murdering a police officer. A key difference between my study and the work of Ewanation et al (2021) relates to the incident described at trial; in their work, Ewanation and colleagues (2021) used a videotaped mock trial that involved a civilian accused of killing a police officer during a UoF incident. The defendant testified that the police were using excessive force during his attempted arrest and claimed to have killed the officer in an act of self-defence.…”
Section: Police Legitimacycontrasting
confidence: 96%
See 4 more Smart Citations
“…This conflicts with previous jury research conducted by Ewanation, Maeder, and Yamamoto (2021), who found that the more legitimate participants believed the police to be, the more likely they were to find a defendant guilty of murdering a police officer. A key difference between my study and the work of Ewanation et al (2021) relates to the incident described at trial; in their work, Ewanation and colleagues (2021) used a videotaped mock trial that involved a civilian accused of killing a police officer during a UoF incident. The defendant testified that the police were using excessive force during his attempted arrest and claimed to have killed the officer in an act of self-defence.…”
Section: Police Legitimacycontrasting
confidence: 96%
“…However, neither the APLS nor the police feeling thermometer were significantly related to jurors' verdicts or perceptions of the officer's UoF. This conflicts with previous jury research conducted by Ewanation, Maeder, and Yamamoto (2021), who found that the more legitimate participants believed the police to be, the more likely they were to find a defendant guilty of murdering a police officer. A key difference between my study and the work of Ewanation et al (2021) relates to the incident described at trial; in their work, Ewanation and colleagues (2021) used a videotaped mock trial that involved a civilian accused of killing a police officer during a UoF incident.…”
Section: Police Legitimacycontrasting
confidence: 87%
See 3 more Smart Citations